ENGAGE: Guided Activity-Based Gaming in Neurorehabilitation after Stroke: A Pilot Study - Ann Reinthal; Kathy Szirony; Cindy Clark; Jeffrey Swiers; Michelle Kellicker; Susan Linder (Stroke Research and Treatment)
Introduction. Stroke is a leading cause of disability in healthy adults. The purpose of this pilot study was to assess the feasibility and outcomes of a novel video gaming repetitive practice paradigm, (ENGAGE) enhanced neurorehabilitation: guided activity-based gaming exercise. Methods. Sixteen individuals at least three months after stroke served as participants. All participants received concurrent outpatient therapy or took part in a stroke exercise class and completed at least 500 minutes of gaming. Primary baseline and posttest outcome measures included the Wolf motor function test (WMFT) and the Fugl-Meyer assessment (FMA). ENGAGE uses a game selection algorithm providing focused, graded activity-based repetitive practice that is highly individualized and directed. The Wilcoxon signed ranks test was used to determine statistical significance. Results. There were improvements in the WMFT (𝑃=0.003) and the FMA (𝑃=0.002) that exceeded established values of minimal clinically important difference. Conclusions. ENGAGE was feasible and an effective adjunct to concurrent therapy after stroke.